Accounting for receptor flexibility and enhanced sampling methods in computer aided drug design - Sinko, William (2013)
Protein flexibility plays a major role in biomolecular recognition. In many cases it is not obvious how molecular structure will change upon association with other molecules. In proteins these changes can be major, with large deviations in overall backbone structure, or they can be more subtle as in a side chain rotation. Either way the algorithms that predict the favorability of biomolecular association require relatively accurate predictions of the bound structure to give an accurate assessment of the energy involved in association. Here we review a number of techniques that have been proposed to accommodate receptor flexibility in the simulation of small molecules binding to protein receptors. We investigate modifications to standard rigid receptor docking algorithms, and also explore enhanced sampling techniques, and the combination of free energy calculations and enhanced sampling techniques. The understanding and allowance for receptor flexibility are helping to make computer simulations of ligand protein binding more accurate. These developments may help improve the efficiency of drug discovery and development. Efficiency will be essential as we begin to see personalized medicine tailored to individual patients, which means specific drugs are needed for each patient’s genetic makeup.